Upland Farmers' Comprehension of Pictorial Messages on Environmental Protection - R. S. Gravoso; T. H. Stuart (Journal of Applied Communications, 2000)
This study was conducted to explore upland farmers’ comprehension of pictorial messages on environmental protection. Eighteen visuals dealing with interrelated topics on environmental protection applied in the uplands were used in the study. Data were gathered through individual interviews and focus group discussion. Results showed that except for the line drawing and reverse reproduction, the visuals were not significantly different in terms of comprehensibility. Age was inversely related to visual comprehension. Educational attainment, visual exposure, and knowledge of environmental protection positively influenced visual comprehension.